A Dança Experimental e a inclusão de alunos com deficiência intelectual: possibilidades para as aulas de Educação Física nos primeiros anos do ensino fundamental. - Raquel Cristina Ramos de Oliveira (2020)
This work aimed to propose Experimental Dance as a methodological strategy for the inclusion of students with intellectual disability in Physical Education classes in elementary school, as many times Physical Education teachers face difficulties to include these students in their classes. Experimental Dance is a methodological proposal for teaching dance developed by Ph.D professor Drª. Isabel Coimbra. This proposal aims at creating new possibilities for moving and dancing, bringing about a practice that allows social inclusion. As a research methodology, the qualitative approach in the action-research model has been adopted to support the elaboration, application and analysis of a pedagogical intervention carried out in a school in the Municipal Education Network of Belo Horizonte ("Escola Municipal Professora Maria Mazarello"). The target audience was pupils from two first-cycle classes in the afternoon shift, being one a first-year class, and the other a third-year class. A didactic unit of eight classes for teaching dance, based on the methodology of Experimental Dance adapted for child audience, has been developed and applied within the annual planning of the Physical Education classes. The data collection process took place by means of participant observation and narratives written by the teacher / researcher in teaching experience diaries. Image records by means of pictures and filming were also used in order to produce material to assist the data analysis as well as for the production of the final product (teaching materials) The results showed that the use of the Experimental Dance methodology in Physical Education classes favored the participation and learning of the whole class, including the students with intellectual disability. The didactic material produced in this research can be accessed at: www.dancaexperimentalnaescola.wordpress.com/home/.